The contemporary factors shaping the professional identity of occupational therapy lecturers: narratives in education, representation and regulation - O'Shea, John (2017)
Occupational therapy (OT) lecturers are at the interface between student education and training and professional practice and therefore have unique insights into the contemporary factors shaping their professional identity and that of the profession. Two main contemporary and interrelated factors have been identified. Firstly, neoliberalist government policies which encourage the marketisation of health and social care provision, which has implications for how the profession is defined and for professional autonomy and values, ways of working, education and training. Secondly, how knowledge is constructed and used within evidence based practice and whether this is compatible with an emerging occupational therapy body of knowledge. These factors are being played out in the fields of representation, regulation and higher education, shaping OT lecturer professional identity and therefore approaches to teaching and learning. This was understood as a structure and agency relationship based on Bourdieu’s theories on ‘Habitus’, ‘Field’ and ‘Capital’ (Bourdieu 1998, 1990, 1977). To do this, nine narrative inquiry focused interviews of occupational therapy lecturers from two universities were carried out. These narratives were understood within wider organisational contexts using a document analysis. A thematic analysis was applied to both interviews and documents. Five main themes have been identified: professional identity and artistry; professional and philosophical body of knowledge; doing research, evidencing practice and the neoliberal agenda; the representation and regulation of the College of Occupational Therapists (COT) and the Health Care and Professions Council HCPC); and moving into new ways of working – the selling of OT. These have implications for the development of OT professional habitus, the relationship between COT and the profession and approaches to teaching and learning.